OA13 Developing sustainable community partnerships to provide ongoing bereavement support. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Groom, Jane
Abstract : Background: This project was developed within an urban home-based palliative care service. It commenced in response to the recognition that acutely grieving people needed long term, broad-based community support, and the need for death education in the community. Aim: It was hoped that bereavement support groups could be relocated from a clinical environment to the community, so that bereaved people could access support in their neighbourhoods, develop supportive local connexions and be introduced to a variety of resources. This would result in developing community partnerships, provide death education, assist in normalising death, dying and grief and in redressing the 'death taboo' in society. Method: Once the concept was approved by the community palliative care service, local community centres were identified, connexions made and discussions held regarding building partnerships to provide bereavement support. Two community centres responded enthusiastically and partnerships have slowly developed. Results: After 2 years, feedback from bereaved carers has consistently endorsed the move to community centres. Staff at one centre have now offered administrative support, requested 'open' grief support groups and grief education sessions. Staff from the other centre have requested a joint memorial service and training in loss and grief for staff. Conclusion: Developing sustainable community partnerships takes time and has required Significant evolutional learning. In particular, it must not become dependent on the specific personnel driving the project and there is a need to develop further protocols and 'embed' the practice. This is an organic process which will continue to grow in response to further development of the partnership.